Is Scissoring a Metaphor for Disconnecting a Relationship? - Chu, Hosang; Kang, Jungyun; Lee, Minhwan; Kim, Hakkyun (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
A great deal of attention has surrounded the role of embodied cognition in human judgments; however, it has received very little research attention, especially in the marketing field. This research is based on the idea that the act of cutting can activate perceptions of severing relationships, as well as eliciting a sense of independence. Study 1 showed that consumers are less likely to adopt a close friendâs opinion when they engage in the act of cutting an object with scissors. Study 2 demonstrated that people are less likely to trust the reviews of online communities while cutting a piece of string with scissors. These lowered intentions to adopt othersâ opinions appeared to be mediated by increased psychological distances between the self and the information provider. In other words, people who engage in the act of scissoring unconsciously weaken or disconnect themselves from the information providers, thereby choosing not to adopt othersâ opinions. This research identifies the link between the physical activity of cutting and the mental disconnection concerning social relationships. The results provide implications in setting up an integrative framework of the consumer decision-making process involving embodied cognition.Â Â Â Â Â Â Â